Cultural Shock Experience and The Adaptation Process: Phenomenology in Regional Student-Athletes in Jakarta - Khoiruningrum, Lulu; Ariyani, Mira; Juriana; Akbar, Zarina; Maulana, Herdiyan (Faculty of Psychology, UIN Sunan Gunung Djati, Bandung Indonesia, 2025)
Moving to a new environment is a challenge for migrants in adjusting to a new culture that often causes cultural shocks. Regional students who also play the role of athletes face the dual challenge of academic and sporting demands. This study aims to understand the experience of cultural shocks and how the adaptation process is experienced by regional students from Papua who study in Jakarta. The approach used in this study is qualitative with phenomenological methods. The participants in this study are two regional student-athletes from Papua who continue their studies at the State University of Jakarta. The results of the study showed that participants felt happy and full of hope because they managed to enter a university in Jakarta. Participants began to find it difficult to deal with cultural issues such as discomfort. Through social support, participants are able to adapt well in Jakarta.